Theory and Applications of Models of Computation : 12th Annual Conference, TAMC 2015, Singapore, May 18-20, 2015, Proceedings - Jain, Rahul; Jain, Sanjay; Stephan, Frank; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 12th Annual Conference on Theory and Applications of Models of Computation, TAMC 2014, held in Singapore, in May 2015. The 35 revised full papers presented were carefully reviewed and selected from 78 submissions. The papers treat all topics relating to the theory and applications of models computation, for example recursion theory and mathematical logic; computational complexity and Boolean functions; graphy theory; quantum computing; parallelism and statistics; learning, automata and probabilistic models; parameterised complexity.
Recursion theory and mathematical logic -- Computational complexity and Boolean functions -- Graph theory -- Quantum computing -- Parallelism and statistics -- Learning, automata and probabilistic models -- Parameterised complexity.
Keywords: Computer science; Computer software; Logic design; Data structures (Computer scienc; Mathematical Logic and Formal Languages; Mathematics of Computing; Algorithm Analysis and Problem Complexity; Logics and Meanings of Programs; Data Structures and Information Theory